Small cuts, big questions: the impact of incision length in minimally invasive robotic cardiac surgery - Thomas E. Rubino; Ariana Jackson; Martin Winter; Kristian Punu; Syed Faaz Ashraf; Keith Dufendach; Nicholas Hess; Rachel Deitz; Stephen D. Waterford; Stephen D. Waterford; David Kaczorowski; David Kaczorowski; et al. (Frontiers in Cardiovascular Medicine, 2025)
IntroductionEvidence on incision lengths for ports and cardiopulmonary bypass (CPB) cannulation in robotic cardiac surgery is limited. This study aimed to assess these metrics and influencing factors.Methods204 patients underwent robotic mitral valve repair (MVR) (54.9%), totally endoscopic coronary artery bypass grafting (TECAB) (30.9%), and minimally invasive direct coronary artery bypass grafting (MIDCAB) (14.2%). Total incision length (TIL) was measured intraoperatively and defined as the sum of thoracic incisions, portholes, and incisions for cannulation. In both univariate and multivariate analyses, TIL was calculated based on demographic and intraoperative variables. Additionally, TIL was linked with postoperative outcomes.ResultsThe median length of thoracic access incisions and ports was 11.5 (5.0–51.0) cm, while for cannulation access, it was 5.0 (3.0–13.0) cm. The median total incision length was 16.5 (10.0–62.0) cm. Thirteen pre- and intraoperative variables were associated with TIL on univariate analysis. Multivariate analysis revealed that BMI (p = 0.003), procedure type (p < 0.001), conversion to sternotomy (p < 0.001), technical challenges (p = 0.034) and total procedure time (p < 0.001) were associated with extended incision length. Multivariate testing additionally showed an association of TIL with blood transfusion (p = 0.004) and hospital stay (p < 0.001).ConclusionsIncision length in robotic cardiac surgery is primarily linked to obesity, procedure type, surgical technical problems, conversion to sternotomy, and procedure time. Longer incisions are associated with an increased number of blood transfusions and longer hospital stay